Microstructural transformation of GO to rGO by ascorbate acid green-agent enhanced using sonication method - Masruroh; Freygieon Ogiek Rizal Sukma; Kormil Saputra; Nandang Mufti; Kusumandari; Anton Prasetyo; Rachmat T Tjahjanto; Dionysius J D H Santjojo (Materials Research Express)
Reduced graphene oxide (rGO) was successfully synthesized from graphene oxide (GO) using ascorbic acid as a reducing agent, combined with a sonication process to improve microstructural transformation and enhance optical properties. The primary objectives of this study were to evaluate the role of ascorbic acid in altering the microstructure of rGO and to examine the effect of sonication duration on the band gap. Characterization of particle size distribution and band gap was carried out using PSA and UV–vis, while changes in microstructure, crystallization, and morphology were analyzed using XRD, Raman spectroscopy, and SEM/EDX. The results showed that increasing the sonication duration decreased the particle size of rGO significantly, contributing to microstructural transformation. The decrease in the bandgap of rGO was also confirmed through UV–vis characterization. FTIR analysis showed a decrease in the absorption intensity of the O=C=O (2200–2450 cm ^−1 ), C–O (1024–1150 cm ^−1 ), and O–H (3650–3800 cm ^−1 ) peaks, indicating a decrease in oxygen groups. SEM showed a change in the morphology of the compact GO surface to a looser and folded rGO, with a decrease in the oxygen ratio detected by elemental mapping. The increase in the intensity of the D band in the Raman spectrum indicated an increase in structural defects due to the reduction of oxygen groups. Crystallite size calculations from Raman and XRD revealed that rGO had a smaller crystallite size than GO, where rGO with a sonication duration of 120 min had a smaller crystallite size than rGO with 180 min, indicating an expansion of the sp ^2 domain. The combination of ascorbic acid and sonication proved effective in reducing GO to rGO with significant improvements in material characteristics.